Positive association between cerebral grey matter metabolism and dopamine D2/D3 receptor availability in healthy and schizophrenia subjects: An 18F-fluorodeoxyglucose and 18F-fallypride positron emission tomography study. (27th May 2020) - Mitelman, Serge A.; Buchsbaum, Monte S.; Christian, Bradley T.; Merrill, Brian M.; Buchsbaum, Bradley R.; Mukherjee, Jogeshwar; Lehrer, Douglas S.
Abstract: Objectives: Overlapping decreases in extrastriatal dopamine D2 /D3 -receptor availability and glucose metabolism have been reported in subjects with schizophrenia. It remains unknown whether these findings are physiologically related or coincidental. Methods: To ascertain this, we used two consecutive 18 F-fluorodeoxyglucose and 18 F-fallypride positron emission tomography scans in 19 healthy and 25 unmedicated schizophrenia subjects. Matrices of correlations between 18 F-fluorodeoxyglucose uptake and 18 F-fallypride binding in voxels at the same xyz location and AFNI-generated regions of interest were evaluated in both diagnostic groups. Results: 18 F-fluorodeoxyglucose uptake and 18 F-fallypride binding potential were predominantly positively correlated across the striatal and extrastriatal grey matter in both healthy and schizophrenia subjects. In comparison to healthy subjects, significantly weaker correlations in subjects with schizophrenia were confirmed in the right cingulate gyrus and thalamus, including the mediodorsal, lateral dorsal, anterior, and midline nuclei. Schizophrenia subjects showed decreased D2 /D3 -receptor availability in the hypothalamus, mamillary bodies, thalamus and several thalamic nuclei, and increased glucose uptake in three lobules of the cerebellar vermis. Conclusions: Dopaminergic system may be involved in modulation of grey matter metabolism and neurometabolic coupling in both healthy human brain and psychopathology. Hyperdopaminergic state in untreated schizophrenia may at least partly account for the corresponding decreases in grey matter metabolism.